The Effect of Oral N-Acetyl Cysteine Administration on Acute Kidney Injury Patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Akbar, Hersusiad; Novadian; Mgs Irsan Saleh (HM Publisher, 2023)
Background: Acute kidney injury (AKI) is a clinical condition characterized by a rapid decline in kidney function that includes structural damage (injury) or malfunction (impairment). AKI is a common complication that occurs in 5-10% of patients due to various underlying etiologies. One of the underlying pathophysiology of AKI is the role of discharge reactive oxygen species (ROS), which causes injury to kidney cells. From various studies, it has been reported that N-acetylcysteine (NAC) has anti-inflammatory and antioxidant effects and has an effect on reducing serum creatinine values. Methods: This research is an open randomized clinical trial without control involving 30 patients at Dr. Mohammad Hoesin General Hospital, Palembang, who were all given intervention in the form of NAC 1200 mg/day, starting in September – October 2023. This study aimed to determine the role of NAC in reducing serum creatinine values in patients with acute kidney injury at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Data analysis was carried out using SPSS 21 univariate and bivariate. Results: From the research results, it was found that the average age of patients was 53.9 years, involving 21 males (70%, N=30) and 9 females (30%, N=30). The most common causes were prerenal and then renal (53.3% and 46.7%). The initial serum creatinine level was found to be 2.12± 0.79 mg/dL (n = 30 samples), and after administration of the intervention, the mean serum creatinine level was 1.28± 0.63 mg/dL (n = 30 samples). By using a paired t-test, there was a decrease in serum creatinine levels significant (p=0,012). Conclusion: NAC administration to patients with acute kidney injury of pre-renal or post-renal causes has a statistical effect on reducing serum creatinine values in patients with acute kidney injury at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia.